2020
DOI: 10.1016/j.ausmj.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Perceived Threat of COVID-19 on Variety-Seeking

Abstract: The COVID-19 pandemic has significantly influenced our daily and social lives as well as our consumption patterns. This paper focuses on the relationship between the COVID-19 threat and variety-seeking. Based on several theories, including reactance theory and terror management theory, we predict that the perceived threat of COVID-19 will increase the tendency to choose more and different options in multiple choice settings. Firstly, two empirical studies demonstrate that variety-seeking in food and stationery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

8
2

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 62 publications
(102 reference statements)
5
87
0
3
Order By: Relevance
“…Participants in the car accident information II condition did not report the perceived threat of car accidents; they reported only their perceived threat of the virus after reviewing the provided information. At the end of the survey, all participants were asked to rate their perceived threat of the two items, based on B€ ohm and Pfister 2005and Kim (2020), using the same scale: "In your opinion, is coronavirus a serious threat?" and "In your opinion, how life-threatening is coronavirus?"…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the car accident information II condition did not report the perceived threat of car accidents; they reported only their perceived threat of the virus after reviewing the provided information. At the end of the survey, all participants were asked to rate their perceived threat of the two items, based on B€ ohm and Pfister 2005and Kim (2020), using the same scale: "In your opinion, is coronavirus a serious threat?" and "In your opinion, how life-threatening is coronavirus?"…”
Section: Methodsmentioning
confidence: 99%
“…Then they were asked to indicate how they perceived the threat of the virus on four items (e.g., what are the chances of you getting infected with the coronavirus?) based on Kim (2020) and Kim et al (2020) along 7-point scales (1 = extremely low, 7 = extremely high; Cronbach's α = 0.80). Second, participants were asked to imagine that they were booking a restaurant and found that one option was a private dining restaurant, as shown in Fig.…”
Section: Study 1: Showing the Main Prediction ( H1 mentioning
confidence: 99%
“…After that, participants were asked to rate their perceived threat on two items (e.g., “In your opinion, is coronavirus a serious threat?”) based on Kim (2020) and Kim and Lee (2020) on a seven-point scale (1 = not at all serious/not at all life-threatening, 7 = very serious/very life-threatening, Cronbach’s α = .744). However, only participants in the COVID-19 + car accident condition were asked to rate their perceived threat of car accidents before rating their perceived threat of the virus along the same scale (Cronbach’s α = .774, n = 98) in order to make the salient comparison between two statistics.…”
Section: Study 1: Testing H1a H2 and H3mentioning
confidence: 99%